Ultra‐High Optical Transparency of Robust, Graded‐Index, and Anti‐Fogging Silica Coating Derived from Si‐Containing Block Copolymers. Issue 6 (2nd May 2013) - Sim, Dong Min; Choi, Min‐Jae; Hur, Yoon Hyung; Nam, Boae; Chae, Geesung; Park, Jong Hyun; Jung, Yeon Sik
<x xml:space="preserve">Abstract</x> A graded‐index anti‐reflection coating with high optical transmittance, a rapid anti‐fogging capability, and excellent robustness is fabricated via the stacking of Si‐containing block copolymers and simple oxidation. The porosity in the nanostructured silica layers can easily be controlled by changing the fraction of the Si‐containing block in the block copolymers. The high optical transparency can be maintained in harsh chemical, mechanical, and thermal environments, suggesting that the coating will be especially advantageous for outdoor applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>